Information Technology Competencies: A Performance Booster for Organizations - Syed Zain ul Abdin; Ali Junaid Khan; Shahzad Ali Gill; Tanveer Ahmed (iRASD Journal of Management)
The purpose of this study is to examine the influence of information technology competencies on financial performance, followed by organizational performance. The primary data collection technique was used to collect the data from 165 IT officers and top managers from Pakistan. Structural equation modelling was applied using Smart PLS 3 to examine the hypothesized model. The direct findings reveal that all three components of IT competencies are statistically significant in organizational performance. Among the three components, information technology infrastructure is the strongest predictor of organizational performance. Further, organizational performance is statistically significant in determining financial performance. There are no direct significant influences of IT competencies toward financial performance. Indirect results show that all three components of IT competencies are statistically significant. IT infrastructure is the strongest predictor of financial performance through organizational performance. Moreover, this study reveals that IT competencies are not merely sufficient to maintain financial performance. Additionally, the firm is also required to focus on complementary indicators such as innovation, quality, customer satisfaction, customer retention, and reduction of operating cost—which are generated by proper utilization of IT competencies.